Cartel Evidence Protects Consumers Under Indonesian Competition Law: Pembuktian Kartel Melindungi Konsumen dalam Hukum Persaingan Usaha Indonesia - Indra Putra Setiadi; Alvandri Christian Rahmat Gulo; Ribka Eklesia (Indonesian Journal of Law and Economics Review, 2026)
General Background: Market regulation is a fundamental legal instrument for maintaining fair business practices, economic efficiency, and public welfare. Specific Background: Cartels are classified as hardcore violations because they distort market mechanisms, raise prices, reduce product quality, restrict choice, and create barriers for new entrants. Knowledge Gap: The main challenge lies in proving secret cartel arrangements, particularly because direct evidence is often unavailable and enforcement still tends to emphasize a conduct-based approach rather than measurable consumer harm. Aims: This study examines mechanisms for proving cartel practices in Indonesian business competition regulation and analyzes how such proof supports consumer protection. Results: The study shows that cartel proof may rely on direct evidence, circumstantial evidence, economic analysis, parallel pricing, market allocation indicators, and plus factors. Indonesia applies both per se illegal and rule of reason approaches, while the quality of proof determines whether enforcement can prevent excessive pricing, declining product quality, and reduced consumer choice. Novelty: The study proposes a shift toward a consumer harm-based approach that places consumer loss as a central indicator in cartel assessment. Implications: Strengthening economic analysis, institutional capacity, indirect evidence use, and integration with consumer protection mechanisms is necessary to build a fair, competitive, and welfare-oriented market system. Highlights: Circumstantial indicators and economic analysis are crucial because secret agreements are rarely documented. Parallel pricing, market allocation, and plus factors can support legal assessment of collusive coordination. A consumer harm-based approach aligns enforcement with welfare, fairness, and market efficiency. Keywords: Cartel, Competition Law, Consumer Protection